TEACHING WRITING RECOUNT TEXT BY USING SCRAPBOOK THROUGH PROJECT BASED LEARNING IN THE EIGHT GRADE OF SMP NEGERI 8 KEDIRI - Agustina, Intan Yuritanti (Jurnal Pendidikan Bahasa Inggris Proficiency, 2021)
This research was carried out to answer about the preparation, implementation, students’ response, and students’ writing in teaching writing recount text by using scrapbook through project-based learning since corona virus pandemic. The design was descriptive qualitative. The data collecting method were interview, observation, questionnaire and documentation. The result of this research showed that the preparation had been supported by the sets of equipment such as by syllabus, lesson plan, learning model, technique, material, media, and assessment. Then, the implementation was implemented in six steps. Then, the students’ responses showed in percentage 92%. It meant that the students gave the positive responses. While, the students’ written showed that all the students has completed 100% the writing task. All the students’ value above minimum criteria of mastery learning. From the result finding, it showed that teaching writing by using scrapbook through project-based learning was good to improve students’ writing ability.